Les points d’articulation entre homéopathie et oncologie conventionnelle - Olivier Schmitz (Anthropologie & Santé)
Several studies have revealed a greater unconventional medicines usage rate in people living with cancer than by other patient categories. The characteristics of cancer, the uncertainties about its evolution as well as the side effects of its treatments are reasons pushing patients toward unconventional therapies. Among these, homeopathy is frequently used. It benefits from a good reputation in the management of some cancer patients’ needs partly ignored by conventional oncology treatments. This exploratory article aims to enlighten what homeopathy treatments can offer to cancer patients, and the way those treatments are combined with conventional treatments. The data analysed come from about twenty ethnographic interviews, conducted with people treated for a cancer using homeopathy. Some elements of the homeopathic treatment organisation, as well as some representations associated with its remedies, suggest that homeopathy can provide some support to patients, especially in their fight against stress and uncertainty that derives from cancer and conventional treatments.